Perancangan Sistem Absensi Guru Menggunakan Android (Studi Kasus : SMAN 17 Kab. Tangerang) - Didi, Mas; Yaser Arafat, Muhammad (CV. Shofanah Media Berkah, 2023)
Android-Based Teacher Attendance Information System at SMA NEGRI 17 KAB. TANGERANG, is a system that makes it easier for teachers at SMA NEGRI 17 KAB. TANGERANG in carrying out teaching activities filling in Teacher Attendance Data can be done through a cellphone, besides that based on Android the teacher can access absences via cellphone in a timely manner and is very easy to use and can reduce cheating in absenteeism, besides that administrators can see the teacher’s attendance system in order to facilitate teacher payroll. Therefore an information technology-based system is needed to fix the weaknesses of the old system, the purpose of this research is to build an attendance system at SMA NEGRI 17 KAB. TANGERANG which will provide convenience and better and more efficient data management in the implementation of education at SMA NEGRI 17 KAB. TANGERANG, identify problems, needs and build an information system according to needs. The research method used is a data collection method in the form of research consisting of observation, interviews and documentation studies as well as literature studies. The object-oriented system design method (OOAD) is carried out by designing the proposed system model. With this system, the menu can only be accessed by certain users, namely teachers and administrators. Based on the results of this study, an Android-based information system has been developed with a case study at SMA NEGRI 17 KAB. TANGERANG. Where in building this system used system development tools, namely Data Flow Diagrams (DFD), Context Diagrams, Entity Relationship Diagrams (ERD) and Flowcharts and using the programming language PHP and HTML and MySQL as the database.